The Effect of Students’ Perceptions on Civic Education Learning on the Mastery of Concepts - Ratnaningsih Ratnaningsih; Rini Triastuti; Dewi Gunawati (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
Nowadays, quality learning from teachers is an important factor in preparing graduates who are able to compete competitively. The relationship of the millennial students and technology transforms the way they get to know the world. Therefore, achievement, guidance and motivation for the current generation is a challenge. Students' perceptions are directly related to self-concept, motivation, effort, and help in finding behaviors. A perception is one’s response resulting from a stimulus received. Students’ learning processes cannot be separated from perceptions as a process of understanding information. Teachers must be able to develop a strategy that ensures learning conducted by teachers is in accordance with what the students expect and desire.  A good student's initial perception of the material being studied makes students enthusiastic in participating in learning.  A good perception of the object will affect motivation and desire to learn, which will affect the students’ mastery of concepts. Students’ perceptions can contribute to their mastery of concepts in civic learning. This research aims to determine the significant effect of students' perceptions of learning civics on their mastery of concepts. The research was conducted on 64 students. The instrument was tested for validity and reliability. The data were then analyzed using the One-Way Anova test. The results showed students' perceptions of civic education learning significantly influences their mastery of concepts.